2001
DOI: 10.1364/ao.40.003640
|View full text |Cite
|
Sign up to set email alerts
|

Design of efficient lightpipes for illumination by an analytical approach

Abstract: We present the concept of principal sections of a lightpipe to analyze the propagation of light through the lightpipe by total internal reflection. Only the principal sections determine the acceptance angle and thus help in the identification of regions where the leakage occurs first. Use of principal sections for analysis leads to a significant reduction in the design effort. We present an analysis of several commonly used lightpipe configurations, e.g., straight and single circular bend, and different cross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…5(d), the solutions converge on the bend ratio R. This result is in agreement with the findings of Ref. [10] even though that study was for constant thickness single-spherical-bend lightpipes. The bend ratio incorporates the thickness of the lightpipe through r 2 into the convergence; therefore, it is a better measure of the étendue or throughput of the lightpipe.…”
Section: D Transfer Efficiency Casesupporting
confidence: 92%
See 1 more Smart Citation
“…5(d), the solutions converge on the bend ratio R. This result is in agreement with the findings of Ref. [10] even though that study was for constant thickness single-spherical-bend lightpipes. The bend ratio incorporates the thickness of the lightpipe through r 2 into the convergence; therefore, it is a better measure of the étendue or throughput of the lightpipe.…”
Section: D Transfer Efficiency Casesupporting
confidence: 92%
“…Additionally, Ref. [10] found that R ≤ n for best lightpipe transfer efficiency, with lesser R values being optimal. In this study R ~ 1.15, which is obviously less than the index of refraction of the acrylic.…”
Section: D Transfer Efficiency Casementioning
confidence: 99%
“…When a spot light source is located at one end on the longitudinal center axis of a cylindrical light pipe, the spatial profile of the light output at the other end has a peak at the center axis while a square light pipe has nearly a flat spatial profile. It had been confirmed theoretically and experimentally [13,14]. This difference in the light transport property between the cylindrical and square tube is considered to cause the difference in the number of the reflection on the surface of the scintillator.…”
Section: Dependence Of Light Output On the Z-positionmentioning
confidence: 82%
“…The result is a set of windows allowing visualization of each virtual image rather than a virtual space freely showing all image spots. The phenomenon is called the "virtual windows effect" [11]. The virtual images that cannot be observed from the specific walls belong to the second kind of void virtual images.…”
Section: A Location Of the Virtual Images And Virtual Polygonsmentioning
confidence: 99%
“…Moreover, it is difficult to avoid the statistical noise of using a Monte Carlo raytracing algorithm. So many analytical methods are developed to design and analyze the light pipe to make up for the deficiency of the commercial software [10][11][12]. In 1963, Chen et al developed the first analytical method of analyzing a straight light pipe with a square cross section and with one point source in the center of the input end [13].…”
Section: Introductionmentioning
confidence: 99%